“Conocimiento de lactancia materna del personal hospitalario y de parturientas atendidas en el hospital regional de Loreto Iquitos 1994” - Chujandama García, Juan Segundo (1994)
This research work is a study descriptive V J with prospective data collection. It aims to determine the level of knowledge about breastfeeding of the hospital staff who work in the service of obstetrics and neonatology of parturients at Loreto Regional Hospital. For the collection of data was carried out a encuesta• Dise ~ adas for such purposes, and after analysis and applying the statistical test of chi square and with the respective significance level; is came to the conclusion that the personal in study to retrieved, a qualifying of good on the knowledge of nursing mother. It is recommended that breastfeeding exclusively should be promoted in all hospitals and places where will cater to pregnant women.